KESADARAN DAN MINAT SANTRI UNTUK MELAKSANAKAN IBADAH UMRAH MELALUI WEBSITE DAN MEDIA SOSIAL: Studi Kasus Santri Pondok Pesantren Nurul Wafa Kecamatan Sukarame, Kabupaten Tasikmalaya - Hasan Basri; Yuda Fazan Aprlilian; Annisa Nur Aeni (ARMUZNA : Jurnal Manajemen Haji dan Umrah (MHU), 2024)
Abstract Many students have quite extensive knowledge regarding religious knowledge regarding the Hajj and Umrah rituals, but the implementation of awareness among the students at the Nurul Wafa Islamic Boarding School, Sukarame District, Tasikmalaya Regency is not yet fully aware of the practice and implementation, so the interest of the students at the Nurul Wafa Islamic Boarding School, Sukarame District , Tasikmalaya Regency is also classified as still low in carrying out Hajj and Umrah rituals. The purpose of this research is to determine the awareness and interest of the students of the Nurul Wafa Islamic Boarding School, Sukarame District, Tasikmalaya Regency in carrying out the Hajj and Umrah rituals and to find out how to increase the awareness and interest of the students of the Nurul Wafa Islamic Boarding School, Sukarame District, Tasikmalaya Regency in carrying out the Hajj and Umrah rituals. The research that the researcher conducted was qualitative research with a descriptive approach that revealed visible symptoms from looking for facts, especially regarding the awareness and interest of students at the Nurul Wafa Islamic Boarding School, Sukarame District, Tasikmalaya Regency to carry out the Umrah pilgrimage. The research results show that there are several factors to increase the awareness and interest of students in carrying out the Hajj and Umrah Manasik, namely as follows: Education about the Principles of Implementing the Hajj and Umrah Manasik, Introduction to Products and Services for the Implementation of the Hajj and Umrah Manasik, Collaboration with the Ministry of Religion for Hajj Affairs, Promotion Benefits and Advantages of Hajj and Umrah Funds, Providing Incentives or Incentives, Parental Involvement, Role Model, Role of Facilitation for Opening Hajj and Umrah Accounts, Simulation Activities, Evaluation and Feedback